REPRESENTASI PEREMPUAN DALAM NOVEL-NOVEL PRAMOEDYA ANANTA TOER - Yulianeta Yulianeta; Nor Hasimah Ismail (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2022)
Pramoedya Ananta Toer, through her social reality novels, presents ideas filled with messages of the struggle for and appreciation of the values of humanity. One of these ideas is the representation of women, presented in Bumi Manusia, Gadis Pantai, Midah Si Manis Bergigi Emas, Larasati, Arok Dedes, and Cerita Calon Arang. These six novels were analyzed using feminist literary criticism. Using qualitative method, this study reveals and describes 1) the position of female characters in their relationship with the other characters; 2) the struggle of female characters in their relationship with the other characters; and 3) the factors that support and hinder the struggle of female characters in Pramoedya Ananta Toer's novels. Based on the results, the women in the six novels put an effort in dismantling (deconstructing) the dominance of patriarchal ideology, promoting familialism as well as gender equality, and favoring the ideology of women in general.